Decentralized Control for Self-driving Cars That can Freely Move on Two-dimensional Plane - Kano, Takeshi; Iwamoto, Mayuko; Ueyama, Daishin (Collective Dynamics, 2020)
In the current traffic rules, cars have to move along lanes and to stop at red traffic lights. However, in the future when all cars become completely driverless, these traffic rules may vanish and cars may be allowed to move freely on two-dimensional plane by avoiding others like pedestrian flow. This innovation could greatly reduce traffic jams. In this study, we propose a decentralized control scheme for future self-driving cars that can freely move on two-dimensional plane, based on the social force model widely used as the model of pedestrian flow. The performance of the proposed scheme is validated via simulation. Although this study is still conceptual and does not consider realistic details, we believe that it paves the way to developing novel traffic systems.